Method for preparing lithium manganese iron phosphate positive electrode material by using titanium dioxide production by-product

The preparation of lithium manganese iron phosphate material through titanium dioxide by-products and combined with ball mill modification liquid and thermal adjustment improvement treatment, the performance problems of lithium manganese iron phosphate positive electrode material at high temperature and high magnification are solved, and the circulation capacity retention rate and capacity performance are achieved Excellent performance.

CN119240641APending Publication Date: 2025-01-03GUANGXI JINMAO TITANIUM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411213032.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have poor performance in circulation capacity retention, and it is difficult to achieve balance and coordination of capacity performance under high temperature and high magnification conditions, which limits the efficiency of the product.

Method used

The primary body of lithium manganese iron phosphate is prepared by titanium dioxide production by-products, and the treatment is improved through ball mill modification liquid and thermal regulation, combined with the coordination and coordination of carbon nanotubes, graphene, nanosilicon dioxide and other materials to optimize the material structure and performance .

Benefits of technology

The circulation capacity retention performance of lithium manganese iron phosphate cathode material is significantly improved, and the capacity performance balance and coordination is achieved under high temperature and high magnification conditions, improving the efficiency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020756190000131
    Figure BDA0005020756190000131
  • Figure BDA0005020756190000141
    Figure BDA0005020756190000141
  • Figure BDA0005020756190000161
    Figure BDA0005020756190000161
Patent Text Reader

Abstract

The invention relates to a method for preparing a lithium manganese iron phosphate positive electrode material by using a titanium dioxide production by-product, which comprises the following steps: carrying out ball-milling improvement treatment on a lithium manganese iron phosphate primary body and a ball-milling modification liquid according to a weight ratio of 5: 3 at a ball-milling rotation speed of 1500r / min for 2 hours, and after the treatment is finished, obtaining a ball-milling improved primary body agent, namely the lithium manganese iron phosphate positive electrode material disclosed by the invention. According to the lithium manganese iron phosphate positive electrode material disclosed by the invention, the lithium manganese iron phosphate primary body prepared from the by-product of titanium dioxide production is matched with the ball-milling modified liquid and the positive electrode material obtained through thermal regulation improvement treatment, and the ball-milling modified liquid and the thermal regulation improvement treatment are coordinated and synergic; the lithium manganese iron phosphate positive electrode material of the product has excellent cycle capacity retention rate performance, and the capacity performance of the product is improved in a balanced and coordinated manner under the conditions of high temperature and high rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium iron manganese phosphate positive electrode materials, and in particular to a method for preparing lithium iron manganese phosphate positive electrode materials by utilizing byproducts produced by titanium dioxide production. Background Art

[0002] Titanium dioxide, also known as titanium dioxide, is an important inorganic pigment. The main industrial processes for preparing titanium dioxide are sulfuric acid method and chlorination method. The main by-product of the sulfuric acid method for preparing titanium dioxide is ferrous sulfate, which contains a variety of metal impurities and hydrolyzed titanium sulfate impurities with different degrees of hydrolysis. Through impurity removal treatment, it can be used as a raw material for lithium-ion battery positive electrode materials, which not only solves the serious backlog problem of by-product ferrous sulfate, but also meets the development needs of the battery industry.

[0003] The lithium manganese iron phosphate positive electrode material prepared by the prior art has poor cycle capacity retention performance, and it is difficult to achieve balanced and coordinated improvement in the capacity performance of the product under high temperature and high rate conditions, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing lithium iron manganese phosphate positive electrode material using by-products of titanium dioxide production, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material by using a byproduct of titanium dioxide production, comprising the following steps:

[0007] Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production:

[0008] (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture;

[0009] (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent;

[0010] (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body;

[0011] Step 2, the lithium manganese iron phosphate primary body and the ball-milled modified liquid are ball-milled at a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and the treatment is completed to obtain a ball-milled improved primary body agent;

[0012] Step 3, subjecting the improved initial agent to thermal conditioning treatment after ball milling, and after the treatment, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained;

[0013] The specific steps of thermal regulation improvement are as follows:

[0014] The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

[0015] Preferably, the impregnation pressure for sufficient impregnation is 10-15 MPa, and the impregnation time is 35-45 min.

[0016] Preferably, the preparation method of the ball milling modified liquid is:

[0017] S11: stirring and modifying the carbon nanotubes in a modifier in an amount 3-5 times the total amount of the carbon nanotubes, washing with water, filtering and drying after the modification is completed, to obtain a modified carbon nanotube agent;

[0018] The preparation method of the modifier is as follows:

[0019] S111: immersing the nano-silica into a yttrium nitrate solution with a volume of 3-5 times the total volume of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent.

[0020] S112: 1-3 parts of carboxymethyl cellulose are added to 4-7 parts of 8% sodium dodecylbenzene sulfonate solution, and then 2-4 parts of nano silicon dioxide and 1-2 parts of stearic acid are added and mixed to obtain a modifier;

[0021] S12: irradiating the graphene in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and then the irradiation ends;

[0022] 3-5 parts of irradiated graphene and 4-7 parts of sodium citrate solution are evenly mixed, and then 2-4 parts of wollastonite and 1-2 parts of silane coupling agent KH560 are added and mixed to obtain a graphene liquid;

[0023] S13: The modified carbon nanotube agent and graphene liquid are mixed in a weight ratio of 2:5 and ultrasonically treated. The ultrasonic power is 350-400 W and the ultrasonic time is 20-30 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

[0024] Preferably, the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power of the immersion ultrasonic treatment is 300-350 W, and the ultrasonic time is 15-25 min.

[0025] The mass fraction of the sodium citrate solution is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.

[0026] Preferably, the preparation method of the impregnation conditioning solution is:

[0027] S101: heating the nano-bentonite to 210-220°C at a rate of 1-3°C / min, keeping the temperature for 10-15min, then heating it to 350-360°C at a rate of 2-5°C / min, keeping the temperature for 2-5min, and finally air cooling it to room temperature;

[0028] S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

[0029] Preferably, the mass ratio of the modified impregnating agent and the nano-bentonite in S101 is (5-7):2.

[0030] Preferably, the modified impregnating agent comprises the following raw materials in parts by weight:

[0031] 2-5 parts of aluminum silicate fiber, 4-7 parts of chitosan solution, 1-3 parts of lanthanum chloride solution, 2-4 parts of sodium lignin sulfonate and 0.25-0.45 parts of hydroxyapatite.

[0032] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.

[0033] Preferably, the specific operation steps of the thermal improvement treatment are:

[0034] First, heat to 210-220℃ at a rate of 1-3℃ / min, keep warm for 20-25min, then heat to 750-780℃ at a rate of 2-5℃ / min, keep warm for 5-10min, and finally air cool to room temperature at a rate of 1-2℃ / min.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The lithium iron manganese phosphate positive electrode material of the present invention adopts the lithium iron manganese phosphate primary body prepared by titanium dioxide production byproduct, and is combined with ball milling modification liquid and thermal regulation improvement treatment to obtain the positive electrode material. The ball milling modification liquid and the thermal regulation improvement treatment are coordinated and matched to enhance the efficiency. The lithium iron manganese phosphate positive electrode material of the product has excellent cycle capacity retention rate performance, and the capacity performance of the product under high temperature and high rate conditions is well balanced and coordinated. The ball milling modification liquid adopts carbon nanotubes treated with a modifier, and the modifier adopts nano silicon dioxide treated with an yttrium nitrate solution, and then combined with carboxymethyl cellulose. Graphene is irradiated with protons to stimulate its activity, and then mixed with sodium citrate solution, wollastonite, and silane coupling agent KH560 to obtain graphene liquid. Graphene is coordinated with wollastonite raw materials, and the flaky structure is combined with needle-shaped wollastonite to intersperse the reinforcement system. Carbon nanotubes and nano-silicon dioxide with high specific surface area are coordinated with graphene liquid, thereby Coordinate and enhance the product's capacity performance under high temperature and high rate conditions, and optimize the product's cycle capacity retention rate; the ball mill improved initial agent heat regulation improvement treatment adopts impregnation adjustment liquid treatment, and then undergoes heat improvement treatment. The impregnation adjustment liquid is heated to 210-220℃ at a rate of 1-3℃ / min with nano bentonite, and kept warm for 10-15min, and then heated to 350-360℃ at a rate of 2-5℃ / min, kept warm for 2-5min, and finally air-cooled to room temperature. The segmented and step-by-step heat improvement is adopted to enhance the activity of nano bentonite. Efficacy and interlayer spacing of the sheets are then blended and mixed with modified impregnating agents, and coordinated with aluminum silicate fiber, chitosan solution, lanthanum chloride solution, sodium lignin sulfonate and hydroxyapatite. Through the coordination between the raw materials, aluminum silicate fiber and hydroxyapatite are used to improve the nano bentonite together, thereby enhancing the improvement effect of the impregnation regulating liquid on the product system, optimizing the product's excellent cycle capacity retention rate performance, and the product's capacity performance under high temperature and high rate conditions, and at the same time, combined with step-by-step and segmented thermal improvement treatment, the performance of the product is further enhanced. DETAILED DESCRIPTION

[0037] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] A method for preparing a lithium iron manganese phosphate positive electrode material using a byproduct of titanium dioxide production in this embodiment includes the following steps:

[0039] Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production:

[0040] (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture;

[0041] (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent;

[0042] (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body;

[0043] Step 2, the lithium manganese iron phosphate primary body and the ball-milled modified liquid are ball-milled at a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and the treatment is completed to obtain a ball-milled improved primary body agent;

[0044] Step 3, subjecting the improved initial agent to thermal conditioning treatment after ball milling, and after the treatment, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained;

[0045] The specific steps of thermal regulation improvement are as follows:

[0046] The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

[0047] The impregnation pressure for sufficient impregnation in this embodiment is 10-15 MPa, and the impregnation time is 35-45 min.

[0048] The preparation method of the ball milling modified liquid of this embodiment is:

[0049] S11: stirring and modifying the carbon nanotubes in a modifier in an amount 3-5 times the total amount of the carbon nanotubes, washing with water, filtering and drying after the modification is completed, to obtain a modified carbon nanotube agent;

[0050] The preparation method of the modifier is as follows:

[0051] S111: immersing the nano-silica into a yttrium nitrate solution with a volume of 3-5 times the total volume of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent.

[0052] S112: 1-3 parts of carboxymethyl cellulose are added to 4-7 parts of 8% sodium dodecylbenzene sulfonate solution, and then 2-4 parts of nano silicon dioxide and 1-2 parts of stearic acid are added and mixed to obtain a modifier;

[0053] S12: irradiating the graphene in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and then the irradiation ends;

[0054] 3-5 parts of irradiated graphene and 4-7 parts of sodium citrate solution are evenly mixed, and then 2-4 parts of wollastonite and 1-2 parts of silane coupling agent KH560 are added and mixed to obtain a graphene liquid;

[0055] S13: The modified carbon nanotube agent and graphene liquid are mixed in a weight ratio of 2:5 and ultrasonically treated. The ultrasonic power is 350-400 W and the ultrasonic time is 20-30 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

[0056] Preferably, the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power of the immersion ultrasonic treatment is 300-350 W, and the ultrasonic time is 15-25 min.

[0057] The mass fraction of the sodium citrate solution in this embodiment is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.

[0058] The preparation method of the impregnation conditioning solution of this embodiment is:

[0059] S101: heating the nano-bentonite to 210-220°C at a rate of 1-3°C / min, keeping the temperature for 10-15min, then heating it to 350-360°C at a rate of 2-5°C / min, keeping the temperature for 2-5min, and finally air cooling it to room temperature;

[0060] S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

[0061] The mass ratio of the modified impregnating agent and the nano-bentonite in S101 of this embodiment is (5-7):2.

[0062] The modified impregnating agent of this embodiment includes the following raw materials in parts by weight:

[0063] 2-5 parts of aluminum silicate fiber, 4-7 parts of chitosan solution, 1-3 parts of lanthanum chloride solution, 2-4 parts of sodium lignin sulfonate and 0.25-0.45 parts of hydroxyapatite.

[0064] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.

[0065] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0066] First, heat to 210-220℃ at a rate of 1-3℃ / min, keep warm for 20-25min, then heat to 750-780℃ at a rate of 2-5℃ / min, keep warm for 5-10min, and finally air cool to room temperature at a rate of 1-2℃ / min.

[0067] Example 1.

[0068] A method for preparing a lithium iron manganese phosphate positive electrode material using a byproduct of titanium dioxide production in this embodiment includes the following steps:

[0069] Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production:

[0070] (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture;

[0071] (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent;

[0072] (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body;

[0073] Step 2, the lithium manganese iron phosphate primary body and the ball-milled modified liquid are ball-milled at a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and the treatment is completed to obtain a ball-milled improved primary body agent;

[0074] Step 3, subjecting the improved initial agent to thermal conditioning treatment after ball milling, and after the treatment, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained;

[0075] The specific steps of thermal regulation improvement are as follows:

[0076] The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

[0077] The immersion pressure for sufficient immersion in this embodiment is 10 MPa and the immersion time is 35 min.

[0078] The preparation method of the ball milling modified liquid of this embodiment is:

[0079] S11: stirring and modifying the carbon nanotubes in a modifying agent in an amount three times the total amount of the carbon nanotubes, washing with water, filtering by suction, and drying after the modification is completed to obtain a modified carbon nanotube agent;

[0080] The preparation method of the modifier is as follows:

[0081] S111: immersing the nano-silica into a yttrium nitrate solution with a volume 3 times the total volume of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent.

[0082] S112: 1 part of carboxymethyl cellulose is added to 4 parts of 8% by mass sodium dodecylbenzene sulfonate solution, and then 2 parts of nano silicon dioxide and 1 part of stearic acid are added and mixed to obtain a modifier;

[0083] S12: irradiating the graphene in a proton irradiation box for 5 minutes, with an irradiation power of 350W, and then ending the irradiation;

[0084] 3 parts of irradiated graphene and 4 parts of sodium citrate solution are evenly mixed, and then 2 parts of wollastonite and 1 part of silane coupling agent KH560 are added and mixed to obtain graphene liquid;

[0085] S13: The modified carbon nanotube agent and graphene liquid are mixed in a weight ratio of 2:5 and ultrasonically treated. The ultrasonic power is 350 W and the ultrasonic time is 20 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

[0086] The stirring speed of the stirring modification treatment is 450 r / min, and the stirring time is 20 min; the ultrasonic power of the immersion ultrasonic treatment is 300 W, and the ultrasonic time is 15 min.

[0087] The mass fraction of the sodium citrate solution in this embodiment is 5%; the mass fraction of the yttrium nitrate solution is 2%.

[0088] The preparation method of the impregnation conditioning solution of this embodiment is:

[0089] S101: heating the nano-bentonite to 210°C at a rate of 1°C / min, keeping the temperature for 10 minutes, then heating it to 35°C at a rate of 2°C / min, keeping the temperature for 2 minutes, and finally air cooling it to room temperature;

[0090] S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

[0091] The mass ratio of the modified impregnating agent and the nano-bentonite of S101 in this embodiment is 5:2.

[0092] The modified impregnating agent of this embodiment includes the following raw materials in parts by weight:

[0093] 2 parts of aluminum silicate fiber, 4 parts of chitosan solution, 1 part of lanthanum chloride solution, 2 parts of sodium lignin sulfonate and 0.25 parts of hydroxyapatite.

[0094] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 3%.

[0095] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0096] First, heat to 210°C at a rate of 1°C / min and keep warm for 20 min. Then heat to 750°C at a rate of 2°C / min and keep warm for 5 min. Finally, air cool to room temperature at a rate of 1°C / min.

[0097] Example 2.

[0098] A method for preparing a lithium iron manganese phosphate positive electrode material using a byproduct of titanium dioxide production in this embodiment includes the following steps:

[0099] Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production:

[0100] (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture;

[0101] (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent;

[0102] (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body;

[0103] Step 2, the lithium manganese iron phosphate primary body and the ball-milled modified liquid are ball-milled at a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and the treatment is completed to obtain a ball-milled improved primary body agent;

[0104] Step 3, subjecting the improved initial agent to thermal conditioning treatment after ball milling, and after the treatment, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained;

[0105] The specific steps of thermal regulation improvement are as follows:

[0106] The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

[0107] The immersion pressure for the present embodiment is 15 MPa and the immersion time is 45 min.

[0108] The preparation method of the ball milling modified liquid of this embodiment is:

[0109] S11: stirring and modifying the carbon nanotubes in a modifying agent in an amount 5 times the total amount of the carbon nanotubes, washing with water, filtering by suction, and drying after the modification is completed to obtain a modified carbon nanotube agent;

[0110] The preparation method of the modifier is as follows:

[0111] S111: immersing the nano-silica into an yttrium nitrate solution with a volume of 5 times the total volume of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent.

[0112] S112: 3 parts of carboxymethyl cellulose are added to 7 parts of 8% sodium dodecylbenzene sulfonate solution, and then 4 parts of nano silicon dioxide and 2 parts of stearic acid are added and mixed to obtain a modifier;

[0113] S12: irradiating the graphene in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and then the irradiation ends;

[0114] 5 parts of irradiated graphene and 7 parts of sodium citrate solution are evenly mixed, and then 4 parts of wollastonite and 2 parts of silane coupling agent KH560 are added and mixed to obtain a graphene liquid;

[0115] S13: The modified carbon nanotube agent and graphene liquid are mixed and ultrasonically treated in a weight ratio of 2:5, with an ultrasonic power of 400 W and an ultrasonic time of 30 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

[0116] The stirring speed of the stirring modification treatment is 550 r / min, and the stirring time is 30 min; the ultrasonic power of the immersion ultrasonic treatment is 350 W, and the ultrasonic time is 25 min.

[0117] The mass fraction of the sodium citrate solution in this embodiment is 8%; the mass fraction of the yttrium nitrate solution is 5%.

[0118] The preparation method of the impregnation conditioning solution of this embodiment is:

[0119] S101: heating the nano-bentonite to 220°C at a rate of 3°C / min, keeping the temperature for 15 minutes, then heating it to 360°C at a rate of 5°C / min, keeping the temperature for 5 minutes, and finally air cooling it to room temperature;

[0120] S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

[0121] The mass ratio of the modified impregnating agent and the nano-bentonite of S101 in this embodiment is 7:2.

[0122] The modified impregnating agent of this embodiment includes the following raw materials in parts by weight:

[0123] 5 parts of aluminum silicate fiber, 7 parts of chitosan solution, 3 parts of lanthanum chloride solution, 4 parts of sodium lignin sulfonate and 0.45 parts of hydroxyapatite.

[0124] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 6%.

[0125] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0126] First, the temperature was raised to 220°C at a rate of 3°C / min and kept at this temperature for 25 min. Then, the temperature was raised to 780°C at a rate of 5°C / min and kept at this temperature for 10 min. Finally, the temperature was air-cooled to room temperature at a rate of 2°C / min.

[0127] Example 3.

[0128] A method for preparing a lithium iron manganese phosphate positive electrode material using a byproduct of titanium dioxide production in this embodiment includes the following steps:

[0129] Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production:

[0130] (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture;

[0131] (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent;

[0132] (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body;

[0133] Step 2, the lithium manganese iron phosphate primary body and the ball-milled modified liquid are ball-milled at a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and the treatment is completed to obtain a ball-milled improved primary body agent;

[0134] Step 3, subjecting the improved initial agent to thermal conditioning treatment after ball milling, and after the treatment, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained;

[0135] The specific steps of thermal regulation improvement are as follows:

[0136] The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

[0137] The immersion pressure for sufficient immersion in this embodiment is 12.5 MPa, and the immersion time is 40 min.

[0138] The preparation method of the ball milling modified liquid of this embodiment is:

[0139] S11: stirring and modifying the carbon nanotubes in a modifying agent in an amount 4 times the total amount of the carbon nanotubes, washing with water, filtering by suction, and drying after the modification is completed to obtain a modified carbon nanotube agent;

[0140] The preparation method of the modifier is as follows:

[0141] S111: immersing the nano-silica into a yttrium nitrate solution with a volume of 4 times the total volume of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent.

[0142] S112: 2 parts of carboxymethyl cellulose are added to 5.5 parts of 8% sodium dodecylbenzene sulfonate solution, and then 3 parts of nano silicon dioxide and 1.5 parts of stearic acid are added and mixed to obtain a modifier;

[0143] S12: irradiating the graphene in a proton irradiation box for 7.5 minutes with an irradiation power of 370 W, and then the irradiation ends;

[0144] 4 parts of irradiated graphene and 5.5 parts of sodium citrate solution were evenly mixed, and then 3 parts of wollastonite and 1.5 parts of silane coupling agent KH560 were added and mixed to obtain graphene liquid;

[0145] S13: The modified carbon nanotube agent and graphene liquid are mixed and ultrasonically treated in a weight ratio of 2:5, with an ultrasonic power of 370 W and an ultrasonic time of 25 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

[0146] The stirring speed of the stirring modification treatment is 500 r / min, and the stirring time is 25 min; the ultrasonic power of the immersion ultrasonic treatment is 320 W, and the ultrasonic time is 20 min.

[0147] The mass fraction of the sodium citrate solution in this embodiment is 6.5%; the mass fraction of the yttrium nitrate solution is 3.5%.

[0148] The preparation method of the impregnation conditioning solution of this embodiment is:

[0149] S101: heating the nano-bentonite to 215°C at a rate of 2°C / min, keeping the temperature for 12.5min, then heating it to 355°C at a rate of 3.5°C / min, keeping the temperature for 3.5min, and finally air cooling it to room temperature;

[0150] S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

[0151] The mass ratio of the modified impregnating agent and the nano-bentonite of S101 in this embodiment is 3:1.

[0152] The modified impregnating agent of this embodiment includes the following raw materials in parts by weight:

[0153] 3.5 parts of aluminum silicate fiber, 5.5 parts of chitosan solution, 2 parts of lanthanum chloride solution, 3 parts of sodium lignin sulfonate and 0.30 parts of hydroxyapatite.

[0154] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 4.5%.

[0155] The specific operation steps of the thermal improvement treatment of this embodiment are:

[0156] First, the temperature was raised to 215°C at a rate of 2°C / min and kept at that temperature for 22.5min. Then, the temperature was raised to 765°C at a rate of 3.5°C / min and kept at that temperature for 7.5min. Finally, the temperature was air-cooled to room temperature at a rate of 1.5°C / min.

[0157] Comparative Example 1.

[0158] The difference from Example 3 is that the ball milling modification liquid treatment is not used.

[0159] Comparative Example 2.

[0160] The difference from Example 3 is that no modified carbon nanotube agent is added to the ball milling modification liquid.

[0161] Comparative Example 3.

[0162] The difference from Example 3 is that no modifier is added to the modified carbon nanotube agent.

[0163] Comparative Example 4.

[0164] The difference from Example 3 is that no nano silicon dioxide agent is added to the modifier.

[0165] Comparative Example 5.

[0166] The difference from Example 3 is that no graphene liquid is added to the ball milling modification liquid for treatment.

[0167] Comparative Example 6.

[0168] The difference from Example 3 is that wollastonite and silane coupling agent KH560 are not added to the graphene liquid.

[0169] Comparative Example 7.

[0170] The difference from Example 3 is that no graphene is added to the graphene liquid.

[0171] Comparative Example 8.

[0172] The difference from Example 3 is that no heat regulation improvement treatment is adopted.

[0173] Comparative Example 9.

[0174] The difference from Example 3 is that the heat conditioning improvement treatment does not use the immersion conditioning liquid treatment.

[0175] Comparative Example 10.

[0176] The difference from Example 3 is that no thermal improvement treatment is used in the thermal regulation improvement treatment.

[0177] Comparative Example 11.

[0178] The difference from Example 3 is that the nano-bentonite S101 is not added to the impregnation adjustment solution.

[0179] Comparative Example 12.

[0180] The difference from Example 3 is that the modified impregnating agent in the impregnation conditioning solution is replaced by deionized water. The products of Examples 1 to 3 and Comparative Examples 1 to 12 were subjected to conventional performance tests, and the test results are as follows

[0181]

[0182]

[0183] It can be seen from Comparative Examples 1-12 and Examples 1-3 that;

[0184] The product of Example 3 has an excellent cycle capacity retention rate at 3C rate. At the same time, under the conditions of 200 and 500 cycles, the cycle capacity retention rate stability of the product is remarkable, and the 3C discharge capacity is still excellently stable at 50 and 65°C.

[0185] If the product does not use either the ball milling modification liquid treatment or the heat regulation improvement treatment, the product performance will deteriorate significantly. If the two treatments are used in combination, the product performance effect will be most significant.

[0186] The ball milling modified liquid was not added with modified carbon nanotube agent, the modified carbon nanotube agent was not treated with modifier, the modifier was not added with nano-silica agent, the ball milling modified liquid was not treated with graphene liquid, wollastonite and silane coupling agent KH560 were not added to the graphene liquid, and graphene was not added to the graphene liquid. The performance of the products tended to deteriorate.

[0187] The modified carbon nanotube agent treated with a modifier obtained by mixing the graphene liquid obtained by the specific method of the present invention with a nano-silicon dioxide agent has the most significant product performance effect, and other methods are not as obvious as the effect of the present invention;

[0188] The performance of the products showed a trend of deterioration when the impregnation conditioning liquid was not used for the thermal conditioning improvement treatment, the nano-bentonite of S101 was not added to the impregnation conditioning liquid, and the modified impregnating agent in the impregnation conditioning liquid was replaced by deionized water. The performance of the products showed a significant trend of deterioration when the nano-bentonite of S101 was not added to the impregnation conditioning liquid, and the modified impregnating agent was replaced by deionized water.

[0189] The present invention further explores the product performance by modifying the impregnating agent;

[0190] Experimental example 1.

[0191] The only difference from Example 3 is that no aluminum silicate fiber is added to the modified impregnating agent.

[0192] Experimental example 2.

[0193] The only difference from Example 3 is that no hydroxyapatite is added to the modified impregnating agent.

[0194] Experimental Example 3.

[0195] The only difference from Example 3 is that no chitosan solution is added to the modified impregnating agent.

[0196] Experimental Example 4.

[0197] The only difference from Example 3 is that no lanthanum chloride solution is added to the modified impregnating agent.

[0198] Experimental Example 5.

[0199] The only difference from Example 3 is that sodium lignin sulfonate is not added to the modified impregnating agent.

[0200]

[0201] It can be seen from Experimental Examples 1-5 that when aluminum silicate fiber is not added to the modified impregnating agent, the performance of the product changes. In the modified impregnating agent, the performance deterioration is most obvious, followed by the absence of hydroxyapatite. At the same time, when chitosan solution, lanthanum chloride solution and sodium lignin sulfonate are not added to the modified impregnating agent, the performance of the product tends to deteriorate to varying degrees. The specific modified impregnating agent composition ratio of the present invention is used, and the product performance effect is the most significant. The use of other methods instead is not as obvious as the effect of the present invention.

[0202] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0203] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing lithium iron manganese phosphate positive electrode material using byproducts of titanium dioxide production, characterized in that: The following steps are involved: Step 1: Preparation of lithium iron manganese phosphate primary body from byproducts of titanium dioxide production: (1) mixing ferrous sulfate, manganese sulfate, ammonium molybdate and polyvinyl pyrrolidone, which are by-products of titanium dioxide production, with water in a weight ratio of 6:3:2:1:8 to obtain a mixture; (2) adding a 10% phosphoric acid solution into the mixture at a weight ratio of 2:5 and stirring to form a precipitate, filtering and drying to obtain a matrix agent; (3) The base agent and LiOH.H2O aqueous solution are mixed and milled in a weight ratio of 1:1, and then calcined at 700°C for 7 hours to obtain a reactant, magnesium nitrate, sodium phosphate and water are mixed in a weight ratio of 2:2:5 to obtain an additive, the additive, the reactant and polyvinyl pyrrolidone are mixed in a weight ratio of 7:3:1, and then ball-milled, and finally calcined at 800°C for 6 hours to obtain a lithium manganese iron phosphate primary body; Step 2: The lithium manganese iron phosphate primary body and the ball-milled modified liquid are subjected to ball-milling improvement treatment at a weight ratio of 5:3, the ball-milling speed is 1500r / min, and the ball-milling is performed for 2h. After the treatment is completed, a ball-milled improved primary body agent is obtained; Step 3, the improved initial agent is subjected to thermal regulation improvement treatment by ball milling, and after the treatment is completed, the lithium manganese iron phosphate positive electrode material of the present invention can be obtained; The specific steps of thermal regulation improvement are as follows: The ball-milled improved primary agent is first immersed in a sufficient amount of impregnation adjustment liquid and fully immersed. After the impregnation is completed, it is filtered and dried, and then heat-improved.

2. According to claim 1, a method for preparing lithium iron manganese phosphate positive electrode material using titanium dioxide production byproducts, characterized in that: The impregnation pressure for full impregnation is 10-15 MPa, and the impregnation time is 35-45 min.

3. The method for preparing lithium iron manganese phosphate positive electrode material using titanium dioxide production byproducts according to claim 1, characterized in that: The preparation method of ball milling modified liquid is as follows: S11: stirring and modifying the carbon nanotubes in a modifier in an amount 3-5 times the total amount of the carbon nanotubes, washing with water, filtering and drying after the modification is completed, to obtain a modified carbon nanotube agent; The preparation method of the modifier is as follows: S111: immersing the nano-silica into an yttrium nitrate solution which is 3-5 times the total amount of the nano-silica, and then ultrasonically treating the solution. After the immersion is completed, the solution is filtered and dried to obtain a nano-silica agent. S112: 1-3 parts of carboxymethyl cellulose are added to 4-7 parts of 8% sodium dodecylbenzene sulfonate solution, and then 2-4 parts of nano silicon dioxide and 1-2 parts of stearic acid are added and mixed to obtain a modifier; S12: irradiating the graphene in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and then ending the irradiation; 3-5 parts of irradiated graphene and 4-7 parts of sodium citrate solution are evenly mixed, and then 2-4 parts of wollastonite and 1-2 parts of silane coupling agent KH560 are added and mixed to obtain a graphene liquid; S13: The modified carbon nanotube agent and graphene liquid are mixed in a weight ratio of 2:5 and ultrasonically treated. The ultrasonic power is 350-400 W and the ultrasonic time is 20-30 min. After the ultrasonic treatment is completed, a ball-milled modified liquid is obtained.

4. The method for preparing lithium iron manganese phosphate positive electrode material using titanium dioxide production byproducts according to claim 3, characterized in that: The stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power of the immersion ultrasonic treatment is 300-350 W, and the ultrasonic time is 15-25 min.

5. The method for preparing lithium iron manganese phosphate positive electrode material using byproducts of titanium dioxide production according to claim 3, characterized in that: The mass fraction of the sodium citrate solution is 5-8%; the mass fraction of the yttrium nitrate solution is 2-5%.

6. The method for preparing lithium iron manganese phosphate positive electrode material using titanium dioxide production byproducts according to claim 1, characterized in that: The preparation method of the impregnation regulating solution is: S101: heating the nano-bentonite to 210-220°C at a rate of 1-3°C / min, keeping the temperature for 10-15min, then heating it to 350-360°C at a rate of 2-5°C / min, keeping the temperature for 2-5min, and finally air cooling it to room temperature; S102: The nano-bentonite of S101 is mixed with the modified impregnating agent to obtain an impregnation regulating solution.

7. A method for preparing lithium iron manganese phosphate positive electrode material using titanium dioxide production byproducts according to claim 6, characterized in that: The mass ratio of the modified impregnating agent and the nano-bentonite of S101 is (5-7):

2.

8. The method for preparing lithium iron manganese phosphate positive electrode material using byproducts of titanium dioxide production according to claim 6, characterized in that: The modified impregnating agent comprises the following raw materials in parts by weight: 2-5 parts of aluminum silicate fiber, 4-7 parts of chitosan solution, 1-3 parts of lanthanum chloride solution, 2-4 parts of sodium lignin sulfonate and 0.25-0.45 parts of hydroxyapatite.

9. A method for preparing lithium iron manganese phosphate positive electrode material using byproducts of titanium dioxide production according to claim 8, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-6%.

10. The method for preparing lithium iron manganese phosphate positive electrode material using byproducts of titanium dioxide production according to claim 1, characterized in that: The specific operation steps of the thermal improvement treatment are: First, heat to 210-220℃ at a rate of 1-3℃ / min, keep warm for 20-25min, then heat to 750-780℃ at a rate of 2-5℃ / min, keep warm for 5-10min, and finally air cool to room temperature at a rate of 1-2℃ / min.

Citation Information

Cited By

  • New energy lithium battery material and preparation method thereof

    CN121306920A